Plasma leptin in female athletes: relationship with body fat, reproductive, nutritional, and endocrine factors - Thong, F. S. L.; McLean, C.; Graham, T. E. (Journal of Applied Physiology, 2000)
The relationship of leptin to thyroid and sex hormones, insulin, energy intake, exercise energy expenditure, and reproductive function was assessed in 39 female athletes. They comprised elite athletes who were either amenorrheic (EAA; n = 5) or cyclic (ECA; n = 8) and recreationally active women who were either cyclic (RCA; n = 13) or taking oral contraceptives (ROC; n = 13). Leptin was significantly lower in EAA (1.7 ± 0.2 ng/ml) than in ECA (2.9 ± 0.3 ng/ml), RCA (5.8 ± 0.9 ng/ml), and ROC (7.4 ± 1.3 ng/ml). Hypoleptinemia in EAA was paralleled by reductions (P < 0.05) in caloric intake, insulin, estradiol, and thyroid hormones. Leptin increased by 40-46% (P < 0.05) in the luteal phase of the menstrual cycle in RCA and ECA. Plasma leptin was similar in the placebo and active pill phases in ROC despite a significant increase in ethinylestradiol. Leptin correlated (P < 0.05) with triiodothyronine and insulin but not with estrogen, energy intake, or exercise energy expenditure. These data suggest that in female athletes 1) leptin may be a metabolic signal that provides a link between adipose tissue, energy availability, and the reproductive axis and 2) sex hormones do not directly regulate leptin secretion.